Construction of an IMiD-based azide library as a kit for PROTAC research. Issue 1 (23rd November 2020) - Liu, Haixia; Sun, Renhong; Ren, Chaowei; Qiu, Xing; Yang, Xiaobao; Jiang, Biao
Abstract : As a promising protein degradation strategy, PROTAC technology is increasingly becoming a new star in cancer treatment. Abstract : As a promising protein degradation strategy, PROTAC technology is increasingly becoming a new star in cancer treatment. Here we report the efficient construction of an IMiD-based azide library via a quick one-step conversion of the existing IMiD-based amine library. This new azide library can act as a kit to endow PROTAC libraries with triazole moieties for various POIs through a highly effective 'click reaction' and then help to rapidly screen out lead degraders that are valuable for drug development. Its power in fleetly identifying potent degraders has been verified on two oncogenic proteins, BCR-ABL and BET, the degraders of which showed comparable potency to or even higher potency than the reported PROTACs in degrading target proteins and effectively inhibiting cancer cell proliferation.